Importance of patient engagement in the conduct of pragmatic multicenter randomized controlled trials: The ADAPTABLE experience. (February 2023) - Marquis-Gravel, Guillaume; Faulkner, Madelaine; Merritt, Greg; Farrehi, Peter; Zemon, Nadine; Robertson, Holly R; Jones, W Schuyler; Kraschnewski, Jennifer
Background/Aims: Actively engaging patient partners in the conduct of trials is crucial to ensure the studies answer genuine, patient-centered, unmet clinical needs, and to facilitate participant recruitment and retention. The aim of this article is to demonstrate the feasibility of patient engagement within a large pragmatic multicenter randomized controlled trial, specifically for the purposes of dissemination of study information/updates and to favorize recruitment and retention. Methods: In the patient-centric, pragmatic ADAPTABLE randomized trial, transparent and timely dissemination of information on the study updates to the trial participants was undertaken to create meaningful engagement and to facilitate retention. A national panel of patient partners, the Adaptors, were directly involved in this information dissemination strategy, and study participants were engaged both nationally and locally to design recruitment methods iteratively during the conduct of the trial. All Adaptors had a lived experience with cardiovascular disease. Results: Adaptors attended bi-weekly meetings facilitated by the director of the study's patient-powered research network. They drafted and/or edited newsletters and ad hoc educational information written in a lay-friendly manner for study participants, which were regularly distributed to the ADAPTABLE community, in addition to online forums where participants could share their experience of their involvement in ADAPTABLE. To spur recruitment, a patient-driven initiative was to draft letters sharing their story, which were distributed by the local study teams. Patient partners thought that using patients' voice to provide their perspectives on why they believed this project was important would be more engaging for prospective participants than traditional approaches. Conclusions: ADAPTABLE's experience has demonstrated the feasibility of engaging patients as partners in the conduct of a large-scale, multi-center, pragmatic randomized controlled trial. Future trials should embrace and iteratively improve this model by engaging patient partners as early as study protocol development and funding applications, and quantify its impact on the effectiveness and value of the trial.